2001
DOI: 10.1155/s1064744901000138
|View full text |Cite
|
Sign up to set email alerts
|

Candidiasis During Pregnancy May Result From Isogenic Commensal Strains

Abstract: Objective: Our laboratory previously demonstrated that asymptomatic vaginal colonization during pregnancy is a factor predisposing patients to subsequent symptomatic vulvovaginal candidiasis. It is unknown whether symptoms result from strain replacement or a change in host relationship to the original colonizing strain. This study was undertaken to determine whether Candida albicans isolates from asymptomatic women could be responsible for subsequent symptomatic vaginitis. Methods: We retained isolates of C. a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0
1

Year Published

2003
2003
2011
2011

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 28 publications
0
6
0
1
Order By: Relevance
“…However, molecular typing of Candida strains derived from vagina and urine has established a clonal relationship (Daniels et al, 2001;Silva et al, 2007) and supports the notion that candiduria similar to bacterial UTIs is mostly an 'ascending' infection and not the result of haematogenous invasion of the urinary-tract system. In hospitalized patients, ascending persistent candiduria in the setting of indwelling urine-draining devices is a very common entity, for which a murine model has not been established to date.…”
Section: Introductionmentioning
confidence: 65%
“…However, molecular typing of Candida strains derived from vagina and urine has established a clonal relationship (Daniels et al, 2001;Silva et al, 2007) and supports the notion that candiduria similar to bacterial UTIs is mostly an 'ascending' infection and not the result of haematogenous invasion of the urinary-tract system. In hospitalized patients, ascending persistent candiduria in the setting of indwelling urine-draining devices is a very common entity, for which a murine model has not been established to date.…”
Section: Introductionmentioning
confidence: 65%
“…Molecular typing of Candida strains derived from the vaginas of pregnant women indicated that the women, who were followed longitudinally through pregnancy, became symptomatic (average time, 14 weeks) with their colonizing Candida strains (62). That study found that five of the eight patients with positive vaginal secretions later showed the presence of the same yeast species in their urine.…”
Section: Distribution Of Candida Spp In Candiduriamentioning
confidence: 98%
“…This paradigm is based on multiple lines of evidence as follows: (i) colonization precedes and is an independent risk factor for disseminated candidiasis (16,21,28,37), (ii) colonization burden correlates with the risk of invasive disease (6,8,22), and (iii) measures that reduce colonization burden reduce the subsequent risk of fungemia (18,29). Innate immunity plays a crucial role in controlling candidal colonization and preventing invasive candidiasis.…”
mentioning
confidence: 99%
“…For example, human ␤-defensins (e.g., human ␤-defensin-1 [h␤D-1] or h␤D-2) are considered integral to innate defense of the integument (3). Likewise, histatins are important molecular effectors of constitutive immunity against Candida in the oral setting (6).…”
mentioning
confidence: 99%